1996
DOI: 10.1074/jbc.271.31.18405
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Cofactor Containing Dr1/p19 Modulates Transcription with TFIIA in a Promoter-specific Fashion

Abstract: An activity that modulated the relative levels of transcription from the adenovirus major late promoter (MLP), and the immunoglobulin heavy chain promoter () was purified as a 90-kDa factor. This factor is suggested to be a heterotetramer of two subunits: a 20-kDa polypeptide identical to the previously described Dr1/ p19 and a novel 30-kDa polypeptide. The Dr1/p19 protein has been characterized as a repressor of transcription, and the 30-kDa protein is related to a recently identified yeast gene proposed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…These results extend the known negative regulatory effects of NC2 on core RNA polymerase II in vitro (16,17,20,(42)(43)(44)(47)(48)(49)(50) and confirm that this regulator can inhibit transcription by RNA polymerase II in vivo.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…These results extend the known negative regulatory effects of NC2 on core RNA polymerase II in vitro (16,17,20,(42)(43)(44)(47)(48)(49)(50) and confirm that this regulator can inhibit transcription by RNA polymerase II in vivo.…”
Section: Discussionsupporting
confidence: 70%
“…1b). A search of the GenBank database (June 7, 1996) revealed that the predicted protein has 39% identity over 99 aa to the NC2␣ (DRAP1) subunit of human NC2 (Dr1⅐DRAP1), which binds to TBP and represses transcription in vitro (16,17,20,(42)(43)(44)(47)(48)(49)(50). The gene encoding the putative yeast NC2␣ protein was named NCB1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracts were prepared immediately thereafter by vigorous vortex mixing with glass beads and, after clarification, were loaded in parallel onto Ni 2ϩ -iminodiacetate-agarose columns. The columns were washed with the same buffer, then eluted using the same buffer containing increasing concentrations of imidazole (20,40,60, and 500 mM), and then stripped with Binding Buffer ϩ 100 mM EDTA. Proteins present in the eluted fractions were analyzed by SDS-PAGE and immunoblotting with an appropriate antibody.…”
Section: Methodsmentioning
confidence: 99%